2021
DOI: 10.1007/s11239-021-02508-1
|View full text |Cite
|
Sign up to set email alerts
|

Routine screening for pulmonary embolism in COVID-19 patients at the emergency department: impact of D-dimer testing followed by CTPA

Abstract: COVID-19 patients have increased risk of pulmonary embolism (PE), but symptoms of both conditions overlap. Because screening algorithms for PE in COVID-19 patients are currently lacking, PE might be underdiagnosed. We evaluated a screening algorithm in which all patients presenting to the ED with suspected or confirmed COVID-19 routinely undergo D-dimer testing, followed by CT pulmonary angiography (CTPA) if D-dimer is ≥ 1.00 mg/L. Consecutive adult patients presenting to the ED of two university hospitals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
10
2
Order By: Relevance
“…Given the low speci city of D-dimer for the diagnosis of PE in COVID-19, multiple studies are consistent with increasing the cut-off point to improve the operational characteristics of diagnostic performance (8,(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 83%
“…Given the low speci city of D-dimer for the diagnosis of PE in COVID-19, multiple studies are consistent with increasing the cut-off point to improve the operational characteristics of diagnostic performance (8,(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 83%
“…D-dimer values were different between adults with PE and those without PE, as has been reported, 17. , 18. but unlike our adult groups, D-dimer values overlapped in the pediatric groups with and without PE.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing this to pre-pandemic studies rates of VTE, among hospitalized non-ICU patients the rate of VTE is estimated to be between 2.8 to 5.6% and rates among ICU patients can be as high as 37% [ 6 - 10 ]. Another recent analysis looking at 445 COVID-19 patients presenting to the ED in whom the treating physician suspected PE observed a rate of 5.8% in this population [ 25 ]. Comparatively, previous studies have shown that the rate of PE in acute chronic obstructive pulmonary disease (COPD) exacerbation is 5.9% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%